2020
DOI: 10.2139/ssrn.3641781
|View full text |Cite
|
Sign up to set email alerts
|

The Individual Welfare Costs of Stay at Home Policies

Abstract: This paper reports the results of a choice experiment designed to estimate the private welfare costs of stay-at-home policies during the COVID-19 pandemic. The study is conducted on a large and representative sample of the Swedish population. The results suggest that the welfare cost of a one-month stay-at-home policy, restricting non-working hours away from home, amounts to 9.1 percent of qSweden's monthly GDP. The cost can be interpreted as 29,600 quality-adjusted life years (QALYs), which roughly correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
2
4
0
Order By: Relevance
“…The results in Figures 2 are further summarized in Table 1 in percentage terms for 19 April 2020, when welfare changes were the most. As is evident, the cumulative welfare loss for the median or the average US county has been about 11 % as of 19 April 2020, which is in line with other studies such as by Andersson et al (2020) who have shown that welfare cost of a stay‐at‐home policy is about 9 % for Sweden.…”
Section: Resultssupporting
confidence: 88%
“…The results in Figures 2 are further summarized in Table 1 in percentage terms for 19 April 2020, when welfare changes were the most. As is evident, the cumulative welfare loss for the median or the average US county has been about 11 % as of 19 April 2020, which is in line with other studies such as by Andersson et al (2020) who have shown that welfare cost of a stay‐at‐home policy is about 9 % for Sweden.…”
Section: Resultssupporting
confidence: 88%
“…The corresponding model implications suggest evidence for about 11% of an average (across days) reduction of welfare during the sample period between February and December 2020 for the average US county. These welfare costs are in line with other studies such as by Andersson et al (2020) who have shown that welfare cost of a stay‐at‐home policy is about 9 % for Sweden, although that paper uses a survey experiment approach different from this paper.…”
Section: Introductionsupporting
confidence: 89%
“…While [16] have evaluated individuals' willingness-to-accept (WTA) to stay home in Sweden, we examine people's WTS in the United States. We show that individuals are willing to stay home for additional five and half weeks to lower the increase in new cases by 100%.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies impose assumptions on individuals' willingness to stay (WTS) at home. Only a few studies have examined how the general public values the costs and benefits of these policies [16,17]. To better understand individuals' willingness to comply with SAH orders, we need to examine their preferences regarding the length of potential lockdowns.…”
Section: Introductionmentioning
confidence: 99%